Centralized E-Comerce Development from The Creativity of Students To Build Santripreneurs - Rahman, Miftahur; Fathudin, Fathudin (JURNAL ISLAM NUSANTARA, 2022)
This study aims to find out about the development of centralized e-commerce applications from the results of the creativity of santripreneurs at the AnNawawi Berjan Islamic Boarding School, Purworejo. The research method used in this study is a combination of qualitative and quantitative methods. Qualitative methods are used in data collection which is carried out by means of literature studies and observations. While the quantitative method is carried out in testing to obtain conclusions. In developing this research system, namely using the waterfall method with the stages of analysis, design and coding. The results of the study show that: Centralized E-Commerce Development Application From Creativity Results To Improve Santripreneurs At AnNawawi Berjan Purworejo Islamic Boarding School is in accordance with Santripreneur requests